2021
DOI: 10.1021/acsomega.1c03125
|View full text |Cite
|
Sign up to set email alerts
|

SOMO–HOMO Conversion in Triplet Cyclopentane-1,3-diyl Diradicals

Abstract: According to the Aufbau principle, singly occupied molecular orbitals (SOMOs) are energetically higher lying than a highest doubly occupied molecular orbital (HOMO) in the electronically ground state of radicals. However, in the last decade, SOMO–HOMO-converted species have been reported in a limited group of radicals, such as distonic anion radicals and nitroxides. In this study, SOMO–HOMO conversion was observed in triplet 2,2-difluorocyclopentane-1,3-diyl diradicals DR3F1, DR4F1, and 2-fluorocyclopentante-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
(30 reference statements)
1
8
0
Order By: Relevance
“…[3,20,26,[28][29][30] Also, some researchers have studied the functional dependency of SHC in DFT calculations and they reported that the unusual electronic configuration is maintained with various functions. [4,37] Thus, DFT is considered to give reliable results about SHC. Further studies on SHC species may provide opportunities for their application in the new field of materials science, such as magnetic materials and OLEDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,20,26,[28][29][30] Also, some researchers have studied the functional dependency of SHC in DFT calculations and they reported that the unusual electronic configuration is maintained with various functions. [4,37] Thus, DFT is considered to give reliable results about SHC. Further studies on SHC species may provide opportunities for their application in the new field of materials science, such as magnetic materials and OLEDs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Abe group reported computational studies on SHC in cyclopentane-1,3-diyl diradicals DR1F1 (X 1 ¼ X 2 ¼ F, n ¼ 1) and DR1HF1 (X 1 ¼ H, X 2 ¼ F, n ¼ 1) at the UB3LYP, UvB97xD or UM06-2X/6-31G(d) level of theory. [37] Moreover, the dihydro-substituted DR1H1…”
Section: Carbenes and Diradicalsmentioning
confidence: 99%
“…triggers an intramolecular electron transfer from the trisarylamine to the radical center, affording a possibility to switch between TPA- More recently, Abe, et al investigated theoretically the electron configurations of diradical compounds based on a macrocyle composed of an anthracene and a 2,2difluorocyclopentane diradical unit, linked together by two diphenylethyne fragments (13, Figure 11). 114,115 In this molecule, the HOMO is mainly localized on the anthracyl unit, with little electronic interaction with the SOMO and SOMO-1 found on the 1,3-diphenylcyclopentane. Both the presence of of the anthracene fragment and fluorine atoms within the cyclopentane unit were shown to be important factors to establish SHI, by raising the energy of the HOMO and stabilizing the SOMO and SOMO-1, respectively.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 94%
“…11). 114,115 In this molecule, the HOMO is mainly localized on the anthracyl unit, with little electronic interaction with the SOMO and SOMO − 1 found on the 1,3-diphenylcyclopentane. Both the presence of the anthracene fragment and fluorine atoms within the cyclopentane unit were shown to be important factors to establish SHI, by raising the energy of the HOMO and stabilizing the SOMO and SOMO − 1, respectively.…”
Section: Design Strategies For Shi Radicalsmentioning
confidence: 96%
“…Irrespective of the spin multiplicity of the present diradicals, the two SOMOs are separated energetically from the highest occupied level by other sets of spin-paired orbitals (Figures 5 and S62 and S63). While a recent theoretical study of Abe et al has proposed a diradical system showing SHI between HOMO and SOMO-1 levels, 94 the electronic configuration of SHI diradical 2 2•2+ appears particularly intriguing. Experiments and calculations suggest that the occurrence of a spatially disjoint pair of MOs energetically below the highest occupied level may contribute to the diradical stability.…”
mentioning
confidence: 99%